2000
DOI: 10.1080/02791072.2000.10400217
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Look at Long-Term Adolescent Recovery: Clinicians Talk to Researchers

Abstract: The purpose of the present article is to identify factors associated with long-term recovery for adolescents. A group of 14 young adults were given semistructured in-depth (one to two hour) interviews. The subjects had been in recovery for two to 16 years. Length of stay in treatment, involvement with self-help groups, psychotropic medication, family support, peer support, spirituality, and other factors were identified as helpful for long-term recovery. A major limitation of this inquiry is that it does not m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 19 publications
3
43
0
Order By: Relevance
“…Conversely, having a recovery-oriented network predicts subsequent decreased alcohol use (e.g., Humphreys, Moos, & Cohen, 1997;Humphreys, Mankowski, Moos, & Finney, 1999;Weisner, Delucchi, & Matzger, 2003). Many former recovering persons report that being in the company of other recovering individuals is helpful (e.g., Granfield & Cloud, 2001;Margolis et al, 2000;Nealon-Woods, Ferrari, & Jason, 1995;Richter, Brown, & Mott, 1991;Trumbetta Mueser, Quimby, Bebout, & Teague 1999). At least one study has reported that the effect of support for abstinence on reduced substance use was stronger than that for general friendship quality .…”
Section: Social Supportsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, having a recovery-oriented network predicts subsequent decreased alcohol use (e.g., Humphreys, Moos, & Cohen, 1997;Humphreys, Mankowski, Moos, & Finney, 1999;Weisner, Delucchi, & Matzger, 2003). Many former recovering persons report that being in the company of other recovering individuals is helpful (e.g., Granfield & Cloud, 2001;Margolis et al, 2000;Nealon-Woods, Ferrari, & Jason, 1995;Richter, Brown, & Mott, 1991;Trumbetta Mueser, Quimby, Bebout, & Teague 1999). At least one study has reported that the effect of support for abstinence on reduced substance use was stronger than that for general friendship quality .…”
Section: Social Supportsmentioning
confidence: 99%
“…A cross-sectional study of 102 women in recovery reported that perceived stress in 16 life domains significantly decreased from prerecovery to recovery (Weaver, Turner, & O'Dell, 2000). An informative, albeit small-scale, exploratory study of drug-dependent persons abstinent for an average of 9 years speaks to the demands recovery places on the individual (Margolis, Kilpatrick, & Mooney, 2000): the majority of subjects reported passing through an initial phase (lasting one to three years) almost solely focused on remaining abstinent, particularly the first year (early recovery). Only once a solid recovery foundation was established could subjects concentrate on "living a normal life," where abstinence was no longer the main focus.…”
Section: Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Fellowship with other recovering persons at 12-step meetings is one of the cornerstones of the 12-step recovery program, cited as a critical source of support by remitting individuals (e.g., Laudet, Savage, and Mahmood, 2002;Margolis, Kilpatrick and Mooney, 2000; NealonWoods, Ferrari, and Jason, 1995). However, the 12-step program of recovery suggests that members do more than attend meetings.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Friends seem to have the largest influence on former addicts to incline to relapse (Chen, Sheth, Elliott, & Yeager 2004;Kandel 1996). For example, study done by Margolis, Kilpatrick & Mooney, (2000) was done on pregnant women among ethnic minorities in North America. This study is based on factors influencing the inclination to relapse such as family and friends.…”
Section: Introductionmentioning
confidence: 99%